Exploring the endogenous governance model for alleviating food insecurity: Comparative analysis of food bank systems in Korea and the USA. (21st November 2014) - Kim, Sunhee
Abstract : Food security is one of the dimensions in reducing poverty. Food bank governance is a key system for increasing food security. Even if thousands of food banks operate around the world by importing the standard US model, a universal standard of governance cannot always be applied to all countries, because actors, networks, and institutions embedded in unique social, economic, cultural, and political contexts retain endogenous properties. Hence, the governance model must reflect the endogeneity each society has. This article aims to theoretically suggest the endogenous governance model and to empirically demonstrate the validity of this model by comparing the governance of food banks in the USA and Korea. Although Korea introduced the US food bank model, the Korean model has been adapted and changed, evolving its own system. To find the difference in endogenous food bank governance between the two countries, we compared the variety of governance models, the institutional context, mode of network, actors' attributes, and time perspective.